Genome-wide analysis of the grapevine stilbene synthase multigenic family: genomic organization and expression profiles upon biotic and abiotic stresses - Vannozzi, Alessandro (BioMed Central, 2012)
BACKGROUND: Plant stilbenes are a small group of phenylpropanoids, which have been detected in at least 72 unrelated plant species and accumulate in response to biotic and abiotic stresses such as infection, wounding, UV-C exposure and treatment with chemicals. Stilbenes are formed via the phenylalanine/polymalonate-route, the last step of which is catalyzed by the enzyme stilbene synthase (STS), a type III polyketide synthase (PKS). Stilbene synthases are closely related to chalcone synthases (CHS), the key enzymes of the flavonoid pathway, as illustrated by the fact that both enzymes share the same substrates. To date, STSs have been cloned from peanut, pine, sorghum and grapevine, the only stilbene-producing fruiting-plant for which the entire genome has been sequenced. Apart from sorghum, STS genes appear to exist as a family of closely related genes in these other plant species. RESULTS: In this study a complete characterization of the STS multigenic family in grapevine has been performed, commencing with the identification, annotation and phylogenetic analysis of all members and integration of this information with a comprehensive set of gene expression analyses including healthy tissues at differential developmental stages and in leaves exposed to both biotic (downy mildew infection) and abiotic (wounding and UV-C exposure) stresses. At least thirty-three full length sequences encoding VvSTS genes were identified, which, based on predicted amino acid sequences, cluster in 3 principal groups designated A, B and C. The majority of VvSTS genes cluster in groups B and C and are located on chr16 whereas the few gene family members in group A are found on chr10. Microarray and mRNA-seq expression analyses revealed different patterns of transcript accumulation between the different groups of VvSTS family members and between VvSTSs and VvCHSs. Indeed, under certain conditions the transcriptional response of VvSTS and VvCHS genes appears to be diametrically opposed suggesting that flow of carbon between these two competing metabolic pathways is tightly regulated at the transcriptional level. CONCLUSIONS: This study represents an overview of the expression pattern of each member of the STS gene family in grapevine under both constitutive and stress-induced conditions. The results strongly indicate the existence of a transcriptional subfunctionalization amongst VvSTSs and provide the foundation for further functional investigations about the role and evolution of this large gene family. Moreover, it represents the first study to clearly show the differential regulation of VvCHS and VvSTS genes, suggesting the involvement of transcription factors (TFs) in both the activation and repression of these genes.